2012
DOI: 10.1093/molbev/mss114
|View full text |Cite
|
Sign up to set email alerts
|

A "Neural" Enzyme in Nonbilaterian Animals and Algae: Preneural Origins for Peptidylglycine  -Amidating Monooxygenase

Abstract: Secreted peptides, produced by enzymatic processing of larger precursor molecules, are found throughout the animal kingdom and play important regulatory roles as neurotransmitters and hormones. Many require a carboxy-terminal modification, involving the conversion of a glycine residue into an a-amide, for their biological activity. Two sequential enzymatic activities catalyze this conversion: a monooxygenase (peptidylglycine a-hydroxylating monooxygenase or PHM) and an amidating lyase (peptidyl-a-hydroxyglycin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 89 publications
(101 reference statements)
0
48
0
Order By: Relevance
“…The PAM-like sequence previously predicted for Chlamydomonas lacked key residues in the PAL domain (Attenborough et al, 2012). Our analysis of sequenced Chlamydomonas expressed sequence tags (ESTs) and the subsequent release of an improved gene model revealed an additional exon, resulting in a domain organization for Cre03.g152850 (hereafter referred to as CrPAM) that is very similar to the mammalian PAM2 isoform (Fig.…”
Section: Identification Of Pam Gene In Chlamydomonasmentioning
confidence: 83%
See 3 more Smart Citations
“…The PAM-like sequence previously predicted for Chlamydomonas lacked key residues in the PAL domain (Attenborough et al, 2012). Our analysis of sequenced Chlamydomonas expressed sequence tags (ESTs) and the subsequent release of an improved gene model revealed an additional exon, resulting in a domain organization for Cre03.g152850 (hereafter referred to as CrPAM) that is very similar to the mammalian PAM2 isoform (Fig.…”
Section: Identification Of Pam Gene In Chlamydomonasmentioning
confidence: 83%
“…The Chlamydomonas genome encodes an active prohormone-processing enzyme A previous phylogenetic study identified PAM-like genes in several green algal genomes including Chlamydomonas reinhardtii, Volvox carteri and Ostreococcus tauri (Attenborough et al, 2012). We report here the characterization of an active peptideamidating monooxygenase in Chlamydomonas (Cre03.g152850).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In contrast to animals from other taxa, pNPs have so far not been found in the sponge Amphimedon queenslandica (Jékely, 2013), indicating that Porifera do not use peptides for paracrine communication. An amidating enzyme involved in pNP maturation, however, has been predicted in A. queenslandica (Attenborough et al, 2012), hinting at the possible presence of pNPs in sponges.…”
Section: Peptides and Relatives Of Ionotropic Rfamide Receptors In Otmentioning
confidence: 99%